Differential Narrow Focusing of Immunodominant Human Immunodeficiency Virus Gag-Specific Cytotoxic T-Lymphocyte Responses in Infected African and Caucasoid Adults and Children - Goulder, Philip J. R. (American Society for Microbiology, 2000)
Cytotoxic T-lymphocyte (CTL) activity plays a central role in control of viral replication and in determining outcome in cases of human immunodeficiency virus type 1 (HIV-1) infection. Incorporation of important CTL epitope sequences into candidate vaccines is, therefore, vital. Most CTL studies have focused upon small numbers of adult Caucasoid subjects infected with clade-B virus, whereas the global epidemic is most severe in sub-Saharan African populations and predominantly involves clade-C infection in both adults and children. In this study, sensitive enzyme-linked immunospot (elispot) assays have been utilized to identify the dominant Gag-specific CTL epitopes targeted by adults and children infected with clade-B or -C virus. Cohorts evaluated included 44 B-clade-infected Caucasoid American and African American adults and children and 37 C-clade-infected African adults and children from Durban, South Africa. The results show that 3 out of 46 peptides spanning p17(Gag) and p24(Gag) sequences tested contain two-thirds of the dominant Gag-specific epitopes, irrespective of the clade, ethnicity, or age group studied. However, there were distinctive differences between the dominant responses made by Caucasoids and Africans. Dominant responses in Caucasoids were more often within p17(Gag) peptide residues 16 to 30 (38 versus 12%; P < 0.01), while p24(Gag) peptide residues 41 to 60 contained the dominant Gag epitope more often in the African subjects tested (39 versus 4%; P < 0.005). Within this 20-mer p24(Gag), an epitope presented by both B42 and B81 is defined which represents the dominant Gag response in >30% of the total infected population in Durban. This epitope is closely homologous with dominant HIV-2 and simian immunodeficiency virus Gag-specific CTL epitopes. The fine focusing of dominant CTL responses to these few regions of high immunogenicity is of significance to vaccine design.